Structural performance of steel beams and frames with slant end-plate connections at elevated temperature. (15th May 2019) - Zahmatkesh, Farshad; Osman, Mohd H.; Talebi, Elnaz; Kueh, Ahmad B.H.; Tahir, Mahmood
Highlights: Early failure of axially restrained steel beams at elevated temperature. Dissipation of thermal expansion in steel beams by using slant end-plate connections. Numerical simulation of slant connections, which is validated by the experiment tests. Thermal performance of slant end-plate connections in frame. Abstract: Thermal expansion remains as one of the most hazardous conditions a restrained steel beam could experience throughout its service life. In this regard, the design of connections plays an important role in dissipating the thermal axial force resulted from such deformation. In this paper, the finite element method (FEM) has been employed to investigate the thermal performance of the steel beam with slant connections under gravity and thermal loads. The numerical outcomes agree very well with the analytical and experimental approaches, thus demonstrating a good reliability of the model to assess the thermal performance of the steel frames with slant end-plate connections. In addition, the proposed and conventional end-plate connections are modelled separately in two 7-storey steel frames to examine their comparative thermal performance. The numerical results conclude that the thermal behaviour of steel frame with the slant end-plate connection is superior to that using conventional since it is capable to dissipate considerably the experienced additional thermal axial forces.